G.E.Morre's ethical theory - "Hutchinson, Brian" (New York, 2007)
Ethical Theory is an authoritative collection of key essays by top scholars in the field, addressing core issues including consequentialism, deontology, and virtue ethics, as well as traditionally underrepresented topics such as moral knowledge and moral responsibility.
Keywords: "Moore, George Edward, 1873-1958-Ethics"